Quality control of surgical and interventional procedures: a review of the CUSUM. Issue 3 (1st June 2007) - Biau, David J; Resche-Rigon, Mathieu; Godiris-Petit, Gaëlle; Nizard, Rémy S; Porcher, Raphaël
Abstract : Background: The report of the CUSUM across surgical and interventional procedures has spawned a fair confusion in the literature. Aim: To assess the use of the CUSUM and to clarify its utilisation in the perspective of future studies. Nature of the study: Retrospective review. Methods: A systematic literature search of Medline was carried out. From each article, data regarding the design of the study, the specialty, the performance criterion, the unit under control, the methodology and the model of the CUSUM used, the use of a graph, the use of a test and the type of test applied were retrieved. Results: 31 studies were found relevant. The design was mainly retrospective for the analysis of the learning curve. The main performance criteria under control were morbidity, mortality and success of the procedure. A graph was plotted in all studies as a CUSUM plot or as cumulative sums of non-negative values. A test was used in 17 studies. Mislabelling of the plot and the test, and misuse of control limits were the most commonly reported mistakes. Conclusion: The CUSUM tool is not yet properly reported in the surgical literature. Therefore, reporting of the CUSUM should be clarified and standardised before its use widens.